THE EFFECT OF TOCILIZUMAB ON THE CONDITION OF BONE TISSUE OF PATIENTS WITH SYSTEMATIC JUVENILE IDIOPATIC ARTHRITIS: RESULTS OF A SERIES OF CASES RETROSPECTIVE STUDY - M. S. Shingarova; E. I. Alexeeva; T. M. Bzarova; R. V. Denisova; S. I. Valieva; M. L. Travina; K. B. Isaeva; М. А. Soloshenko; O. L. Lomakina (Педиатрическая фармакология)
Background. Osteoporosis — a typical manifestation of systemic juvenile idiopathic arthritis (JIA) and aggravation of glucocorticosteroid therapy. High risk of fractures with osteoporosis remains an urgent issue of rheumatology. Objective:  Our aim was to study the effect of tocilizumab on bone tissue with patients having systemic JIA. Methods.  History of children’s disease (< 18 years) with systemic JIA and known results of densitometry of the lumbar spine (L1–L4) before and after 12 months of tocilizumab therapy have been studied. Results.  Anamnesis of 49 patients (including 24 girls) having systemic JIA have been analyzed. The median age of patients was 14 (7; 21), the age of onset of the disease — 4 (1; 14), disease duration — 9 (2; 19) years. High activity of the disease has been noted with all chlidren; 23 (47%) had limitation of functional activity (score on the questionnaire CHAQ). 36 (74%) children took 0.5 mg/kg of glucocorticosteroids  per day orally, 32 (65%) — intravenously. Tocilizumab was applied for all children in a dose of 12 mg/kg 1 time every 2 weeks. Prior to prescribing  tocilizumab, osteoporosis  (Z-score  <-2.5  SD) was detected  with 15 (30%) children, osteopenia (Z-score -1 and -2) — with 14 (29%) children, past bone fractures — with 5 (11%) children. After 1 year of treatment, inactive stage of the disease/remission according to the criteria of C. Wallace was recorded with 100% of patients; physical activity (assessed by CHAQ) increased. Glucocorticosteroids per os dose was decreased to 0.05 mg/kg per day for all patients; pulse therapy was not performed. Along with the therapy, increase in the values of Z-score  from baseline -1.2  (-5.8;  1.9) to -0.7 (-4.7, 3.0) after 12 months of therapy (p <0.001) and mineral bone density — 0.6 (0.3, 1.3) 0.7 (0.4, 1.2) respectively (p <0.001) was observed. New bone fractures were not observed. Conclusion. Therapy that included tocilizumab resulted in positive changes in bone status with patients having systemic JIA.